1996
DOI: 10.1029/95jd02903
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution ammonium ice core record covering a complete glacial‐interglacial cycle

Abstract: High‐resolution ammonium measurements were performed along the Greenland Ice Core Program (GRIP) deep ice core, covering a complete climatic cycle. No overall anthropogenic increase is observed over the last 300 years; however, springtime concentrations have roughly doubled since 1950. Biomass burning is estimated to be a major source for ammonia emissions for preindustrial times. It contributes between 10% to 40% to the total ammonium deposited on the central Greenland ice sheet during the Holocene. No correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
142
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 65 publications
(30 reference statements)
9
142
0
Order By: Relevance
“…The lack of an increase has to be treated a little cautiously, not only because of the noisy signal, but also because the conversion of ammonia to aerosol, and therefore its deposition efficiency, both en route and in Greenland, will have altered as sulfate and nitrate have increased. Nonetheless, at face value, this suggests that Greenland in summer (which dominates the annual budget) is still seeing ammonium from undisturbed (northern) North American ecosystems [34] or from marine sources. Unsurprisingly, ammonium concentrations in Antarctic snow show no anthropogenic trend.…”
Section: Ice-core Records: Anthropogenic Change In Ammoniummentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of an increase has to be treated a little cautiously, not only because of the noisy signal, but also because the conversion of ammonia to aerosol, and therefore its deposition efficiency, both en route and in Greenland, will have altered as sulfate and nitrate have increased. Nonetheless, at face value, this suggests that Greenland in summer (which dominates the annual budget) is still seeing ammonium from undisturbed (northern) North American ecosystems [34] or from marine sources. Unsurprisingly, ammonium concentrations in Antarctic snow show no anthropogenic trend.…”
Section: Ice-core Records: Anthropogenic Change In Ammoniummentioning
confidence: 99%
“…For ammonium, there is no clear recent trend in Greenland [34], although this would have to be discerned from a noisy background, that is largely owing to the dominance of biomass burning spikes in the record [35]. By splitting the annual snowfall into approximately monthly slices, it appears as if an upward trend since 1950 can be observed in the winter/ spring concentrations [34], when Greenland sees a greater proportion of airmasses from Eurasia [36], but not in the summer, when airmasses are most frequently from North America.…”
Section: Ice-core Records: Anthropogenic Change In Ammoniummentioning
confidence: 99%
See 2 more Smart Citations
“…First, it was shown that ammonium profiles, extracted from Greenland ice cores, are useful for reconstructing the history of forest fires from the boreal zone in the past [Legrand et al, 1992]. Furthermore, Fuhrer et al [ 1996] demonstrated that the ammonium level of central Greenland snow, free of sporadic biomass burning inputs, is mainly related to continental biogenic emissions from soils, and no evidence for the existence of a significant marine NH.…”
mentioning
confidence: 99%